Precaution: Oximetry central venous catheter shaft is no longer waterproof when cut - Yamamoto, Tomohiro; Matsuda, Keiichiro; Shiraishi, Shuichi; Schindler, Ehrenfried (Anestezjologia Intensywna Terapia, 2021)
This letter discusses precautions regarding the waterproof structure of the oximetry central venous catheter (CVC) shaft and the risk of blood reflux and leakage that can occur when the catheter shaft is cut. To assess oxygen supply-demand balance [1] and haemodynamics [2], the Swan-Ganz pulmonary artery catheter has been used for perioperative and postoperative management and treatment of critically ill patients for a half a century. In current clinical practice, haemodynamic parameters such as stroke volume (SV) and cardiac output (CO), as well as central venous oxygen saturation (ScvO2), can be measured continuously using a combination of FloTrac Sensor (Edwards Lifesciences Japan Ltd., Tokyo, Japan) [3], Edwards PreSep Oximetry Catheter (Edwards Lifesciences Japan Ltd., Tokyo, Japan) [4], and EV1000 Clinical Platform (Edwards Lifesciences Japan Ltd., Tokyo, Japan) or Vigileo Monitor (Edwards Lifesciences Japan Ltd., Tokyo, Japan) [5, 6]. These methods are less invasive than the Swan-Ganz pulmonary artery catheter, and the changes in the parameter values can be used as an index for perioperative management in both cardiovascular and non-cardiovascular surgeries. In addition, they can be used for the treatment of critically ill patients in the intensive care unit, enabling proactive determination of an appropriate therapy [7]. Compared to intermittent sampling and traditional vital signs alone, continuous ScvO2 monitoring is a more sensitive indicator of tissue perfusion because it reveals the true adequacy of tissue oxygenation, enabling early detection and assessment of clinical response to intervention [7, 8].